2016
DOI: 10.3389/fpls.2016.01272
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis Zinc Finger Protein Increases Abiotic Stress Tolerance by Regulating Sodium and Potassium Homeostasis, Reactive Oxygen Species Scavenging and Osmotic Potential

Abstract: Plant zinc finger proteins (ZFPs) comprise a large protein family and they are mainly involved in abiotic stress tolerance. Although Arabidopsis RING/FYVE/PHD ZFP At5g62460 (AtRZFP) is found to bind to zinc, whether it is involved in abiotic stress tolerance is still unknown. In the present study, we characterized the roles of AtRZFP in response to abiotic stresses. The expression of AtRZFP was induced significantly by salt and osmotic stress. AtRZFP positively mediates tolerance to salt and osmotic stress. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 55 publications
(69 reference statements)
1
37
0
Order By: Relevance
“…RNA-seq analysis show that TaZFP1 regulates photosynthesis, osmolyte metabolism, and ROS-homeostasisrelated genes involved in salt stress (Sun et al, 2019a). AtRZFP enhances salt tolerance by increasing ROS scavenging and maintaining Na + and K + homeostasis (Zang et al, 2016).…”
Section: Roles In Salt Stressmentioning
confidence: 99%
“…RNA-seq analysis show that TaZFP1 regulates photosynthesis, osmolyte metabolism, and ROS-homeostasisrelated genes involved in salt stress (Sun et al, 2019a). AtRZFP enhances salt tolerance by increasing ROS scavenging and maintaining Na + and K + homeostasis (Zang et al, 2016).…”
Section: Roles In Salt Stressmentioning
confidence: 99%
“…Glutathione peroxidase and peroxidase family proteins expression indicates higher response to oxidative stress, glutathione peroxidase activity, metal ions binding & transportation activity [Alzahrani et al 2018; Martinez et al, 2018]. Interestingly, number of transcripts of zinc finger transcription factors and helicase-like transcription factor were expressed in HZFWGs showed their function in various transcription factor activity, sequence-specific DNA and metal ion binding and stress response [Bouain et al, 2014; Zang et al, 2016; Sarwat et al, 2018]. Accompanied number of transcripts of wheat are also expressed those are only involved in different STR.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests these nutrients likely communicate with N-containing metabolites to play a role in cellular osmotic adjustment response and ROS detoxification to oxidative stress induced by heavy/toxic metals (e.g., Mn, Al, Zn) and/or salinity stress in these red maple trees. Furthermore, altered cellular K+/Na+ homeostasis can induce cellular desiccation (i.e., lower cell water content) and signal an osmotic stress response that triggers the regulation of water and nutrient balance, regulation of iWUE, and cellular osmotic adjustment [26,[46][47][48]. Interestingly, McDermot et al [3] found increased foliar Mg, very toxic levels of Mn, and lower chlorophyll and proline in red maple trees growing in low soil pH and low soil organic matter in Newark forests compared to Philadelphia forests.…”
Section: Discussionmentioning
confidence: 99%